Interação e intolerância em torno do assassinato de Marielle Franco nas fanpages direita vive 3.0 e jovens de esquerda: uma abordagem semiótica - Natália Silva Giarola de Resende (2022)
The purpose of this thesis is to analyze how the meanings of intolerant discourses are constructed from the interactions in the posts and comments of the Facebook fanpages Direita Vive 3.0 and Jovens de Esquerda, concerning the death of Rio de Janeiro’s councilwoman Marielle Franco. The research corpus is delimited in six posts and in the first ten most relevant Facebook comments in the periods: (i) from March 14 to 31, 2018, date of Marielle's murder; (ii) from March 14 to 31, 2019, one year of the councilwoman’s death and the arrest of the suspects of the murder; (iii) from October 20 to November 30, 2019, disclosure of the alleged involvement of the president of the republic Jair Bolsonaro with the case. To develop this study, semiotic studies of intolerant discourses were used as theoretical and methodological resources, with notes on identity and otherness, and discursive interactions, both permeated by the characteristics of internet discourse. The mentioned axes fulfilled the task of answering how the enunciative strategies of the intolerant subject that govern the enunciator-enunciatee relationship in the two fan pages are built. Thus, in relation to the discursive interactions, the research results show that the posts of the two pages are governed, above all, by the conquered meaning, aiming at an intentionality, an establishment of a contract, in which the enunciators of the posts lead the enunciatee's meaning of the reading. In addition, the enunciates of the posts present the use of the objectifying camouflage, though we were able to rescue marks of subjectivity in the implicit and explicit posts on both pages. In the comments, we identified two types of subjects, the authorized enunciators, who accept the contract proposed by the post, assuming their position as enunciatee, without changing positions. In this case, the themes of the pair post/comments are the same, but there are discursive increases in the comments, by means of new figures and, also, the enunciatees use the same discursive strategies of the enunciator, the objectifying camouflage. We also highlight the presence of non-authorized enunciators, who, ruled by the random meaning, subvert the theme of the post and establish a polemical situation, with an exchange of turns between enunciator and enunciatees. To do so, they use as a strategy the subjectivating camouflage, with a demarcated I-You. That said, we can deduce that in the intolerant discourses of the two pages there is the establishment of two subjects, an "I", which orders the identity, values and beliefs of their group, and another, seen as the otherness, which should be excluded from social coexistence. We also verified that the discourses of the fan pages present similar strategies, regarding: (i) the construction of the fundamental base level, expressed by the categories identity versus otherness; (ii) the pragmatic and cognitive sanctions, on the narrative level; (iii) the passionate paths of the intolerant subjects, namely: prejudice, in which the subject becomes malevolent towards the other, leading to passions such as indignation, hostility, animosity and hatred and, at the same time, benevolence towards his equals; and the virtualized intolerance itself, in which the subject wants to exclude the other, but cannot, because, he is not in a physical space to concretize to the action. Finally, it is at the discursive level and in the tensivity that we notice disparities in the intolerant strategies of the two fan pages. Direita Vive 3.0 presents as its main theme the immorality of the left, associated with anti-leftism and, especially, the minimization of the death of Marielle Franco. As for tensivity, the death of the councilwoman is governed by the discourse of exercise, through a process of weakening the intensity of the murder. In the Jovens de Esquerda fan page, the theme is also immorality, but to the right, and to the potentialization of Marielle's death, which is seen by these enunciators as an event, being toned up to the maximum. Another difference found in the field of tensivity is that although the intolerant discourses of the two fan pages are governed by triage, starting from a predatory intolerance, the exclusion of otherness has distinct intensities. On the right-wing page, the exclusion of the other is more intense, aiming at the death of the left or rejoicing the death of Marielle Franco, while on the left, the exclusion aims at imprisonment of otherness, therefore, it presents a lower intensity if compared to the other fan page.